Anti-biofilm activity of plant derived extracts against infectious pathogen-Pseudomonas aeruginosa PAO1. Issue 11 (November 2020) - Alam, Khan; Farraj, Dunia A. Al; Mah-e-Fatima, Syeda; Yameen, Muhammad Arfat; Elshikh, Mohamed Soliman; Alkufeidy, Roua M.; Mustafa, Abd El-Zaher M.A.; Bhasme, Pramod; Alshammari, Maryam K.; Alkubaisi, Noorah A.; Abbasi, Arshad Mehmood; Naqvi, Tatheer Alam
Abstract: Background: Biofilm forming ability of Pseudomonas aeruginosa make them vulnerable, because it makes them recalcitrant against various antibiotics. Quorum sensing (QS) is cell density based signaling that helps in bacterial cell–cell communication, which regulated various virulence factors such as pigment and biofilm formation that contribute in the establishment of chronic infections. The interruption of QS is one of the effective approach to control various virulence factors. Present study was intended with the aim to authenticate antibiofilm potential in different solvents based extracts of selected medicinal plant species viz. Berginia ciliata, Clematis grata and Clematis viticella traditionally used by the inhabitants of Himalayan region of Pakistan to treat various pathogenic diseases. P. aeruginosa PAO1, an opportunistic pathogen and involves in various life-threatening infections specifically in immune deficient patients was used as a model pathogen. Methods: Plants were extracted in various organic (ethanol, methanol, acetone, ethyl acetate, hexane, chloroform) as well as in aqueous solvents and their ability to inhibit biofilm was measured. Biofilm of PAO1 was grown in Jensen's medium while growing at 30 °C and crystal violet assay was performed to assess the biofilm inhibiting activity of plant extracts. Results: Solvents play a vital role in extraction of plant components and it was found that the plants in various solvents exhibit different activity against the PAO1 biofilm. Comparatively, 1% methanolic extract of B. ciliata (rhizome with skin), showed more than 80% inhibition of biofilm formation without effecting on the growth of the bacterium. Significant correlation between flavonoids content and antibiofilm activity in methanolic extract revealed the contribution of secondary metabolites in P. aeruginosa (PAO1) biofilm inhibition. Conclusion: Our study revealed that plants under investigation more specifically B. ciliata could be a potential candidate for drug discovery to treat P. aeruginosa PAO1, induced infectious diseases especially for its biofilm treatment.